The phytochemical investigation of five African Croton species: Croton oligandrus, Croton megalocarpus, Croton menyharthii, Croton rivularis and Croton megalobotrys. (December 2020) - Langat, Moses K.; Djuidje, Elvire F.K.; Ndunda, Beth M.; Isyaka, Sani M.; Dolan, Nathalie S.; Ettridge, Gareth D.; Whitmore, Hannah; Lopez, Isabel; Alqahtani, Alaa M.; Atiku, Ibrahim; Lobe, Jules S.; Mas-Claret, Eduard; et al.
Graphical abstract: Highlights: Ent -isopimarane diterpenoids were isolated from C. oligandrus. Ent -clerodane and ent -abietane diterpenoids were isolated from C. megalocaruus. Methoxylated flavones were isolated from C. menyharthii. Acyclic terpenoids were isolated from C. rivularis. Triterpenoids were isolated from C. megalobotrys. Ent -clerodanes were evaluated against the NCI60 panel of human tumour cell lines. Abstract: The chemistry of five African Croton taxa, Croton oligandrus Pierre ex Hutch., Croton megalocarpus Hutch., Croton menyharthii Pax, Croton rivularis Mull.Arg. and Croton megalobotrys Mull.Arg. is described. The undescribed ent -19-hydroxyisopimara-8(9), 15-dien-7-one and ent -isopimara-7(8), 15-dien-16, 19-diol were isolated from the fruits of C. oligandrus, ent -isopimara-7(8), 15-dien-19-yl octadecanoate was obtained from both the fruits and leaves, and ent -19-hydroxyisopimara-8(9), 15-dien-7-one was isolated from the leaves of this species. The undescribed 3, 4, 15, 16-diepoxy-8α-hydroxycleroda-13(16), 14-dien-12 S, 17-olide and (5 S, 9 R, 10 S )-7, 13- ent -abietadien-2-one were isolated from the leaves and roots of C. megalocarpus respectively. Compounds isolated from C. menyharthii, C. rivularis and C. megalobotrys have been reported from other sources. The structures of the compounds were determined using NMR, IR and MS experiments. The absolute configurations of the ent- isopimarane, ent -abietane and ent -clerodane diterpenoids isolated were confirmed by comparing calculated and experimental electronic circular dichroism (ECD) spectra. DP4+ probability calculations were used to assign the configuration at C-8 for 3, 4, 15, 16-diepoxy-8α-hydroxycleroda-13(16), 14-dien-12 S, 17-olide. Epoxy- ent- clerodadiene, 3β, 4β:15, 16-diepoxy-13(16), 14- ent -clerodadien-17, 12 S -olide, 3β, 4β:15, 16-diepoxy-8α-hydroxy- ent- cleroda-13(16), 14-dien-12, 17-olide, 7, 13-abietadien-2-ol, (5 S, 9 R, 10 S )-7, 13- ent- abietadien-2-one, crotonolide E, furocrotinsulolide A, epoxychiromodine, 3β, 4β:15, 16-diepoxy-13(16), 14-ent-clerodadiene and crotohalimaneic acid were selected for screening based on their ability to add diversity to the NCI small molecule compound collection, and were evaluated against the NCI60 panel of human tumour cell lines at 10μM level, but found inactive.